Ship security alert system : a failed effort to protect coastal communities - Timlen, Thomas (2009)
Merchant ships are now equipped with alert systems intended to prevent acts of terrorism. However, local authorities maybe alerted too late to take effective action. Several steps can be taken to tackle the flaws in the current ship security alert system.